1997
DOI: 10.1016/s0005-2736(97)00030-8
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholate stabilizes phospholipid-rich membranes and mimics the effect of cholesterol: investigations on large unilamellar vesicles

Abstract: Ursodeoxycholate is used to treat primary biliary cirrhosis and is incorporated into hepatocyte plasma membranes. Its steroid nucleus binds to the apolar domain of the membrane, in a similar position to cholesterol. Therefore the question arises whether ursodeoxycholate has a similar effect on membrane structure and stability as cholesterol. Using differential scanning calorimetry the thermotropic behavior of egg phosphatidylcholine and dimyristoylphosphatidylcholine were studied after incubation with choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 25 publications
2
29
0
1
Order By: Relevance
“…Like cholesterol, the incorporation of UDC in the cell membrane maintains stability of the lipid double layer and prevents damage caused by chemical stress. 10 The tendency of UDC to form micelles makes it superior in regard to its membrane protection compared with even more hydrophilic triketo bile salts that are not able to form micelles because of their lack of polar and apolar regions. 14 Histological examination supported the results of our previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Like cholesterol, the incorporation of UDC in the cell membrane maintains stability of the lipid double layer and prevents damage caused by chemical stress. 10 The tendency of UDC to form micelles makes it superior in regard to its membrane protection compared with even more hydrophilic triketo bile salts that are not able to form micelles because of their lack of polar and apolar regions. 14 Histological examination supported the results of our previous study.…”
Section: Discussionmentioning
confidence: 99%
“…122,[125][126][127] Stabilization of membrane structures exposed to bile acids has been shown by the addition of ursodeoxycholate or its conjugates. 128,129 Although the nephrotoxicity of bile acids in many clinical conditions has been difficult to identify, functional renal changes and microscopically determined tubular alterations have been shown in patients with obstructive jaundice. 121 Sitprija et al 130 showed that GFR decreased without a change in renal blood flow (RBF) in patients with elevated bilirubin levels (a marker for elevated bile acid levels) of 27 to 40 mg/dL and normal albumin levels (Ն35 g/L).…”
Section: Other Mechanisms Of Renal Injury In the Setting Of Cirrhosismentioning
confidence: 99%
“…It is known that UDCA has multiple mechanisms of action including stabilization of plasma membrane against cytotoxic bile salt-induced cytolysis, 18) and prevention of cytotoxic bile saltinduced apoptosis. 19) Furthermore, cholehepatic shunting of UDCA will promote the removal of cytotoxic bile from bile acid pool.…”
Section: Vil2mentioning
confidence: 99%